Transcranial magnetic stimulation of the left angular gyrus during encoding does not impair associative memory performance. Issue 3 (2nd October 2018) - Koen, Joshua D.; Thakral, Preston P.; Rugg, Michael D.
ABSTRACT: The left angular gyrus (AG) is thought to play a critical role in episodic retrieval and has been implicated in the recollection of specific details of prior episodes. Motivated by recent fMRI studies in which it was reported that elevated neural activity in left AG during study is predictive of subsequent associative memory, the present study investigated whether the region plays a causal role in associative memory encoding. Participants underwent online transcranial magnetic stimulation (TMS) while encoding word pairs prior to an associative memory test. We predicted that TMS to left AG during encoding would result in reduced subsequent memory accuracy, especially for estimates of recollection. The results did not support this prediction: estimates of both recollection and familiarity-driven recognition were essentially identical for words pairs encoded during TMS to left AG relative to a vertex control site. These results suggest that the left AG may not play a necessary role in associative memory encoding. TMS to left AG did however affect confidence for incorrect 'intact' judgments to rearranged pairs and incorrect 'rearranged' judgments to intact pairs. These findings suggest that the left AG supports encoding processes that contribute to aspects of subjective mnemonic experience.